Effect of E-Learning on Capacity Building in the Nigerian Public Sector: A Study of the Anambra State Ministry of Works - S. O. Alokwu (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the effect of e-learning on capacity building in the Nigerian public sector, with particular focus on the Anambra State Ministry of Works between 2020 and 2024. The study was motivated by the increasing need for continuous workforce development in public institutions amidst the growing adoption of digital learning technologies. The specific objectives of the study were to assess the role of e-learning on employees’ technical skills development and to analyze the effect of e-learning on employees’ managerial skills development in the Ministry. The study was anchored on the Technology Acceptance Model (TAM), developed by Fred Davis, which explains users’ acceptance and utilization of technological systems based on perceived usefulness and ease of use. A descriptive survey research design was adopted for the study. The population consisted of 156 staff members of the Anambra State Ministry of Works, and due to the manageable size, a census approach was employed. Data were collected through structured questionnaires and oral interviews, while secondary data were sourced from textbooks, journals, government publications, and online materials. The reliability of the instrument was tested using Cronbach’s Alpha, which yielded a coefficient of 0.84. Data were analyzed using frequency distributions, percentages, weighted mean, and Chi-square (χ²) statistical technique at 0.05 level of significance. Findings revealed that e-learning significantly enhances employees’ technical skills development by improving technical knowledge, understanding of modern technologies, and application of acquired knowledge in daily responsibilities. The study also found that e-learning significantly improves managerial skills development through enhanced leadership, communication, planning, and decision-making abilities among employees. The hypotheses tested showed calculated chi square values of 81.130 and 44.623 respectively, which were greater than the critical table value of 26.296, leading to the rejection of the null hypotheses. The study concluded that e-learning is an effective tool for public sector capacity building and contributes positively to improved employee performance and service delivery in the Anambra State Ministry of Works. The study recommended that the Ministry should strengthen e-learning infrastructure and institutionalize regular digital training programs to improve both technical and managerial competencies among staff.